Critical Thinking: The Need for It Today - Gloria C. Kismadi (Journal of English Language and Culture, 2017)
Critical thinking is not a new concept but one that goes all the way back to more than two thousand years ago when Socrates developed a way of questioning to look into the rationality of how people thought, learned and examined issues that needed answers and solutions.  The development of civilization throughout the ages, however, has always influenced the way people are educated and learn the skills needed in order to understand and deal with questions that come up within contexts that are new and may still be unfamiliar.  In the process of such developments, views with regard to the way people think and reason out issues change to suit the needs and demands of the time.  It is in this manner that critical thinking became ignored in the education of young people. Today, however, critical thinking has been brought back into education, and the reason could very well be that current demands on students make it necessary for them to learn to understand and function rationally in today’s fast-changing world with its varied and multi-complex problems.Developments in technology have brought about unprecedented amounts of information at speeds never before anticipated.  What happens in one small corner of the world is known globally the instant it occurs.  Education that continues to focus only on the teaching of “reading, writing and ‘rithmetic” would be straying off course from the directions that should be taken in order to cope with today’s as well as future needs.  It is for this reason that training in critical thinking should be a vital part of the educational curriculum today. Keywords: Critical thinking, education, curriculum